KOMUNIKASI PENSYARAH KOLEJ KOMUNITI LEDANG DALAM PERLAKSANAAN PEMBELAJARAN SEPANJANG HAYAT - Buang, Zurani; Mohamad, Mimi Mohaffyza (Online Journal for TVET Practitioners, 2018)
Effective communication is very important in life especially in the field of learning. In general, this study was conducted to identify the interpersonal communication skills in lifelong learning, among lecturers of Ledang Community College, Johor. In particular, this study looks at three main aspects of communication namely interpersonal skills, verbal communication and non verbal communication. A total of 36 respondents were selected to answer the questionnaire distributed. They comprise the lecturer of Ledang Community College, Johor. The data were analyzed using mean and average score. The findings show that lecturers of Ledang Community College master the communication skills at a moderate level. The findings also show that there is no significant difference in the mastery of communication among lecturers of Ledang Community College based on their academic qualifications. Some suggestions have also been proposed to enhance interpersonal communication skills among Ledang Community College lecturers who can be implemented for future studies.